Hepatitis B serological changes following allogeneic bone marrow transplantation. Issue 1 (11th July 2012) - Teh, B.W.; Slavin, M.A.; Szer, J.; Sasadeusz, J.J.
Abstract Hepatitis B (HBV) reverse seroconversion (RS) in immunocompromised patients with serological evidence of past HBV infection (hepatitis B surface antigen [sAg] negative, core antibody [cAb] positive) has been reported with increasing frequency following allogeneic hematopoietic stem cell transplant (allo‐HSCT). We performed a retrospective review of serial HBV serological testing in patients who had undergone allo‐HSCT at our center between 2000 and 2006. We identified 12 patients with serological evidence of past HBV, including 1 case of RS. Although 7 of these 12 patients had no changes in serological markers detected after transplantation, 5 of them had declining levels of hepatitis B surface antibodies [sAb], with 2 to < 10 IU/mL. The remaining 4 patients with past HBV had loss of antiHBcAb. An additional 14 patients developed isolated antiHBcAb post allo‐HSCT in the setting of receiving HBV screened (HBsAg, antiHBcAb) negative donor stem cells. Monitoring of HBV serological markers (including antiHBsAb) and HBV DNA levels pre allo‐HSCT in recipients and donors, and post allo‐SCT in recipients, would allow early detection and treatment of RS and identify new acquisition of HBV.